L’apport de la sculpture à la compréhension des fonctions liturgiques - Pascale Chevalier (Les Cahiers de l'École du Louvre)
Within the ecclesial space, sculptures with mainly aniconic content were found on the liturgical furniture: altar, ciborium, cathedra, chancel, ambo, and so on. The combinations of decorations featured elements of repertoires with characteristic layouts. Chasing, engraving, champlevé, bas-relief and openwork spread over the limits of the choir, reinforcing the significance of the sacrificial altar, the seat of the celebrant and the dais from which the Word resounded. The rituals had settings, sculpted milestones that were rarely inscribed and often enhanced by paintings that matched the colourful atmosphere of the church. Rich in information for the researcher, the loquacious pieces of furniture bore symbolic visual messages. The forms of the vestiges and the traces of their layout mapped out functional guidelines or dividing lines. In them, the movements of a liturgy that evolved between the fourth and tenth centuries may be recognised, one whose texts explain few of its details and variations.